SATISFACTION WITH WORKING CONDITIONS AND MENTAL HEALTH OF HEALTHCARE WORKERS ACCORDING TO THEIR SELF-ASSESSMENT - Vsevolod Borovets; Oleh Lyubinets (Acta Medica Leopoliensia)
The ongoing military operations in Ukraine have intensified the pre-existing stress experienced by medical professionals due to the inherent demands of their work.